Contrasting Signals of the Westerly Index and North Atlantic Oscillation over the Drought Sensitivity of Tree-Ring Chronologies from the Mediterranean Basin - Pablo Casas-Gómez; Raúl Sánchez-Salguero; Pedro Ribera; Juan C. Linares (Atmosphere, 2020)
Extreme drought events are becoming increasingly frequent and extended, particularly in Mediterranean drought-prone regions. In this sense, atmospheric oscillations patterns, such as those represented by the North Atlantic Oscillation (NAO) index and the Westerly Index (WI) have been widely proven as reliable proxies of drought trends. Here, we used the Standardized Precipitation–Evapotranspiration Index (SPEI), as a reliable indicator of drought, to investigate the drought sensitivity of tree-ring width data (TRW) from several long-lived tree species (Abies borisii-regis, Abies cilicica, Abies pinsapo, Cedrus atlantica, Cedrus libanii, Pinus nigra, Pinus heldreichii). NAO and WI relations with TRW were also investigated in order to identify potential non-stationary responses among those drought proxies. Our temporal and spatial analyses support contrasting Mediterranean dipole patterns regarding the drought sensitivity of tree growth for each tree species. The spatial assessment of NAO and WI relationships regarding SPEI and TRW showed on average stronger correlations westward with non-stationary correlations between annual WI index and TRW in all species. The results indicate that the drought variability and the inferred drought-sensitive trees species (e.g., C. atlantica) are related to the NAO and the WI, showing that TRW is a feasible proxy to long-term reconstructions of Westerly Index (WI) variability in the Western Mediterranean region. Spatial variability of drought severity suggests a complex association between NAO and WI, likely modulated by an east–west Mediterranean climate dipole.